2020
DOI: 10.1111/ocr.12420
|View full text |Cite
|
Sign up to set email alerts
|

Individualization of the three‐piece base arch mechanics according to various periodontal support levels: A finite element analysis

Abstract: Introduction The orthodontic correction of periodontally compromised dentitions constitutes a huge challenge in the clinical practice of adult orthodontics. The biological and physical distinct features of these conditions require a carefully designed mechanical plan for the successful treatment of these complex cases. Setting and Sample Population A segment of a human maxilla containing the central and lateral incisors, obtained from autopsy, was scanned with microcomputed tomography, and a finite element (FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…It has been recommended that the orthodontic intrusive force of teeth with reduced alveolar bone support should be decreased proportionally to the periodontal surface loss 6,7,10,19 to maintain PDL stress levels similar to the situation without periodontal compromise (correspondent to the R0 models). However, PDL stresses due to the orthodontic intrusion are not precisely represented by the simplified formula σ = F/A.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been recommended that the orthodontic intrusive force of teeth with reduced alveolar bone support should be decreased proportionally to the periodontal surface loss 6,7,10,19 to maintain PDL stress levels similar to the situation without periodontal compromise (correspondent to the R0 models). However, PDL stresses due to the orthodontic intrusion are not precisely represented by the simplified formula σ = F/A.…”
Section: Discussionmentioning
confidence: 99%
“…In periodontally compromised teeth intrusion, the risk of root resorption is more critical since the forces applied to a reduced periodontium generate significantly higher stresses and strains within the periodontal ligament (PDL). 6,7 Clinical studies have already shown that patients with reduced but healthy periodontium can undergo orthodontic treatment without aggravating their periodontal conditions. 8,9 Yet, a reduction in the orthodontic force levels is indicated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…So that it will helps dentists to learn details about the elasticity of periodontal ligament by referring this study. More details about the modelling and simulation of tooth movement can be find in [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%